AN ANALYSIS OF AL-ASALIB AL-BALAGHIYAH AND ITS MEANING IN SURAH AL-FATH / ØªØÙ„ÙŠÙ„ Ø§Ù„Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© ÙˆÙ…Ø¹Ø§Ù†ÙŠÙ‡Ø§ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„ÙØªØ - Fairuz Subakir Ahmad; Anita Nurjanah; Mohammad Ismail; Muhammad Wahyudi (Lughawiyah: Journal of Arabic Education and Linguistics, 2023)
This article aims to analyze the beautiful verses of AsÄlib BalÄghiyyahÂ  and its meaning in Surah Al-Fath, because Surah Al-Fath has Uslub which contains secrets and wisdom of the victory of Muslims, the forgiveness of Allah S.W.T, as well as the events of BÄiâ€™u RidwÄn and Shulhu-l-Hudaibiyyah, by using very beautiful languages and has a high mÄjaz value. Therefore, the writer wants to examine these asÄlib to study the peculiarities and meanings in them. This research used qualitative method by literature review data collection method with an analytical of balÄghah. Therefore, this research began by collecting data from books and documentation. The results of this research state that there are 12 uslÅ«b in Surah Al-Fath. There are 17 same verses with different uslÅ«b, namely verses 1, 2, 3, 4, 5, 6, 10, 11, 12, 14, 17, 18, 20, 21, 22, 27 and 29 consisting of 1 verse of Isti'Ärah Makniyyah, 2 verses of IstiÄrah Tashrihiyyah, 1 verse of Tasybih Tamtsil, 1 verse of KinÄyah, 3 verses of ltifath, 1 verse of ItnÄb, 4 verses of Shiyaghul MubÄlaghah, 1 verse of Ijazul Qashri , 2 verses TibÄqul ÄªjÄz, 2 verses TibÄqus Sulbi, 4 verses Sajaâ€™, and 3 verses MuqÄbalah. The meanings of uslub are Al-MubÄya'ah, Al-Muâ€™Ähadah, Ad-DÄ«n, AttaushÄ«f, Al-IstihzÄ, AliltifÄt, At-Taâ€™kÄ«d, Al-MubÄlagah, AttasyrÄ«f, AttargÄ«b, Attadad, AttashdÄ«q and Al-MuqÄbalah.